Epidermal growth factor receptor mutations in non- small cell lung cancers in a multiethnic Malaysian patient population - Liam, Chong-Kin; Leow, Hwong-Ruey; How, Soon Hin; Pang, Yong-Kek; Chua, Keong-Tiong; Lim, Boon-Khaw; Lai, Nai-Lang; Kuan, Yeh-Chunn; Pailoor, Jayalakshmi; Rajadurai, Pathmanathan (National Cancer Center, Korea, 2014)
In Malaysian patients with NSCLC, the EGFR mutation rate was similar to that in other Asian populations. EGFR mutations were significantly more common in female patients and in never smokers. Never smoking status was the only independent predictor for the presence of EGFR mutations.